A survey of the NHS reporting radiographer workforce in England - Paul Lockwood; Christopher Burton; Theresa Shaw; Nicholas Woznitza (Radiography Open, 2024)
Introduction: At present there is no national register of the population size and scope of reporting radiographers in England. This makes operational workforce and succession planning for sustainable healthcare services in the National Health Service England (NHSE) difficult, affecting implementing NHSE policies and priorities such as 50% of X-rays reported by reporting radiographers and decreasing reporting Turnaround Times (TATs). This survey aimed to establish the workforce population employed as reporting radiographers in NHSE.